Zasada podmiotowego traktowania skazanych w kodeksie karnym wykonawczym z 1997 roku - Stańdo-Kawecka, Barbara (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
During the work on the draft of the 1997 Code of the Execution of Penalties (CEP) much attention was paid to the principle of the treatment of sentenced persons, and particu-larly those serving prison sentences, as subjects. In the Polish penological literature two dimensions of that principle were indicated. The first one referred to the strengthening of the sentenced person’s position in relation to enforcement authorities by means of precise regulations concerning his/her legal status and effective mechanisms for the protection of his/her rights. The second dimension meant the abandonment of forced rehabilitation and providing sentenced persons with the ability to decide freely whether they wanted to partici-pate in correctional interventions. Undoubtedly, the 1997 CEP strengthened the legal status of a sentenced person. As regards the abandonment of forced rehabilitation, the legislator chose a compromise solution according to which the participation in correctional interven-tions was, as a rule, voluntary, but in some cases it was mandatory. Like in other countries, in Poland in the last decade the idea of the public protection against crime played an in-creasingly important role in the criminal policy. In the criminal justice system focused on risk management, the treatment of sentenced persons as subjects requires providing them with reliable information on the possible consequences of their decisions concerning the participation in offered correctional activities. Additionally, it requires providing them with adequate access to empirically proven correctional programmes as well as introducing a transparent system of risk assessment and monitoring during the execution of the imposed penalty or penal measure.
Keywords: osoba skazana; wyrok więzienia; status prawny a osoba skazana; przymusowa rehabilitacja